2020
DOI: 10.5152/tud.2019.19172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rectal mucosa cleansing on acute prostatitis during prostate biopsy: A randomized prospective study

Abstract: I n d e x e d i n P u b M e d , W e b o f S c i e n c e a n d S c o p u s Pankaj M. Joshi and Sanjay B. Kulkarni. A new technique of double-face buccal graft urethroplasty for female urethral strictures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Considering the nature of the passage from the rectal cavity to the prostatic lodge as a clean‐contaminated procedure, a few steps must be considered before a transrectal approach can be performed when attempting to lower the risk of perioperative infectious complications. Rectal preparation by enema is routinely recommended, and even though this practice facilitates a smoother procedure for the urologist, no significant advantage in its use before transrectal biopsy regarding infectious complications has been shown 46 . In contrast, studies have shown that the use of iodine‐povidone for rectal preparation before prostate biopsy, resulted in a lower rate of infectious complications 47 .…”
Section: Methods To Prevent Post‐transrectal Prostate Biopsy Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the nature of the passage from the rectal cavity to the prostatic lodge as a clean‐contaminated procedure, a few steps must be considered before a transrectal approach can be performed when attempting to lower the risk of perioperative infectious complications. Rectal preparation by enema is routinely recommended, and even though this practice facilitates a smoother procedure for the urologist, no significant advantage in its use before transrectal biopsy regarding infectious complications has been shown 46 . In contrast, studies have shown that the use of iodine‐povidone for rectal preparation before prostate biopsy, resulted in a lower rate of infectious complications 47 .…”
Section: Methods To Prevent Post‐transrectal Prostate Biopsy Infectionsmentioning
confidence: 99%
“…Rectal preparation by enema is routinely recommended, and even though this practice facilitates a smoother procedure for the urologist, no significant advantage in its use before transrectal biopsy regarding infectious complications has been shown. 46 In contrast, studies have shown that the use of iodine-povidone for rectal preparation before prostate biopsy, resulted in a lower rate of infectious complications. 47 Furthermore, a 4year prospective study including 3000 patients who were followed prospectively after prostate biopsy, also supported its use in addition to antimicrobial prophylaxis resulting in a lower infection complication rate.…”
Section: Other Interventionsmentioning
confidence: 99%
“…Regarding the non-pharmacologic prophylaxis, rectal povidone-iodine preparation before the biopsy is mandatory to reduce by half the rate of infectious complications [RR 0.47, 95% CI 0.36–0.61]. 59,60…”
Section: Diagnostic Proceduresmentioning
confidence: 99%
“…Regarding the non-pharmacologic prophylaxis, rectal povidone-iodine preparation before the biopsy is mandatory to reduce by half the rate of infectious complications [RR 0.47, 95% CI 0.36-0.61]. 59,60 No differences were found in terms of risk of infection regarding needle guide type, needle type, needle size, or number of anesthetic injections for nerve-blockage. 54 Rectal culture should be performed to avoid infective complications following the procedure and a targeted prophylactic treatment should be started.…”
Section: Prostate Biopsymentioning
confidence: 99%
“…Vasovagal response was defined as bradycardia and hypotension during the biopsy. Acute prostatitis was defined as hospitalization for the first 30 days after biopsy due to urinary tract infection with fever (body temperature higher than 38.5°C) 9) . The definition of sepsis was based on the 2001 International Sepsis Definitions Conference 10) .…”
Section: Evaluation Of Clinical Parametersmentioning
confidence: 99%